Cybersecurity and protection of children's rights (Herald of Journalism, 2023)
Currently, the development of technology and Internet is changing the traditional principles of security, requires a new approach to this issue and the adoption of specific comprehensive measures. The most pressing issue in this direction is related to the protection of children's rights, that is, in particular, with the release of the young generation from Internet addiction and the launch of legal mechanisms to protect them from cyberspace threats.The goal of the research is to conduct a comprehensive study of the problems of protecting children's rights in cyberspace and pay special attention to schoolchildren, including adolescents; since statistics show that children begin to actively use mobile phones and social networks during this period.The article describes the importance of the problem of legal regulation of Internet space, including the fact that the negative impact of Internet for children is growing day by day.This issue concerns human rights defenders and media representatives not only of our country, but also of the whole world. The reasons are also weighty, firstly, it concerns the information protection and security of the young generation, and secondly, it is the protection of the rights of students. The author especially draws attention to such topics as cyberbullying, inciting hatred on the Internet, encroachment on the honor and dignity of students.The article uses methods of collecting statistical data and necessary facts, their analysis, ranking, comparison, as well as infographic.The author, putting forward the issue of cybersecurity of children and their legal literacy in the country, points to the need for legal regulation measures on the part of the state and society. The author of the article comprehensively analyzes foreign regulatory measures in this direction, as well as their best practices. This can be considered as the main results of the study.            Keywords: cyber security, social media, legal regulation, children's rights, legal literacy, cyberbullying.